Hubungan Penyakit Menular, Sumber Air Bersih, Praktik Kebersihan, dan Sanitasi dengan Kejadian Stunting: Studi Kasus Kontrol di Kabupaten Sambas: The Relation of Infectious Diseases, Water Access, Hygiene Practice, and Sanitation with the Stunting: A Case-Control Study in Sambas Regency - Budiastutik, Indah; Pranaka, Resky Nanda; Amaliyah, Nurul; Hediyanti, Giska; Trisnawati, Elly (Amerta Nutrition, 2024)
Background: The main nutritional problem concerned by the Indonesian government is the stunting. This condition is affected by various aspects, mainly caused by infectious diseases, clean and unharmonious living behavior, the availability of drinking water, and environmental sanitation. Objectives: The purpose of this study is to determine the relation of infectious diseases, water access, hygiene practices, and sanitation towards the stunting incidence factors in Sambas Regency. Methods: This research used Ex Post Facto with a case-control design. The study population was residents of Sambas Regency with a total of 535,725 people, a total sample of 241 children aged 0-59 months comprising of 89 respondents as cases and the rest 159 respondents as controls, using inclusion and exclusion criteria both from the control group and from the case group. Data analysis used the chi-square test. Results: The results showed a relation of infectious diseases (p-value=0.000), drinking water sources (p-value=0.000), clean and healthy living behavior (p-value=0.000), and environmental conditions (p-value=0.000) with the stunting incidences. Conclusions: The study concludes that there is a significant relation of infectious disease variables, the drinking water sources, hygiene practices, and environmental conditions with the stunting. It requires control and completion of the stunting cases through environmental sanitation improvement, namely the provision of access to clean water, healthy and clean living behaviors, and good cooperation between the government and the community, in educating people through counseling and socialization of the stunting prevention and management.